Hedonic Wages and Labor Market Search - Hwang, Hae‐shin; Mortensen, Dale T.; Reed, W. Robert (Journal of Labor Economics, 1998)
This article investigates the consequences of labor market search for the theory of hedonic wages. We find that the introduction of search has surprising consequences for the theory of hedonic wages. In particular, we demonstrate that the equilibrium distribution of wage and nonwage amenity bundles generally bears little resemblance to workers' underlying preferences. A consequence of this analysis is that estimates of workers' marginal willingness to pay, derived from the conventional hedonic wage methodology, are biased. In addition, we demonstrate that search generates differences between firm‐level and employee‐level data that can cause substantial deviations in the estimates of hedonic wage equations.